The Development of Soft Ball Sport Through Toss Ball Training in The Athlete Soft Ball - Alimuddin, Alimuddin; Dahlan, Firmansyah (Department of Physical Education, Sport, Health and Recreation, 2020)
Analisys results of the ability to hit softball ball during several months of training since the introduction of soft ball is still very low. The ability to hit the average of the athletes prepared is still very minimal in reaching the target should be a goal and still ranges from 10-25% of the total punch and still can be said this very low level of punch ability this Penelintian aims To know the level of effectiveness of toss ball exercises to increase the ability to hit ball softball athletes softball City Palopo. This study uses a type of correlational Deskriftip Experimental Research which is a research directed to explain the relationship between two variables i.e. free-variable toss ball exercises with variable-bound ability to hit ball softball The athlete softball City Palopo by using the test hit ball softball Elrod batting test. The location of this research is conducted in Palopo. The samples used in this study were all the athletes of the Softball town of Palopo amounted to 15 athletes. Sampling techniques using saturated sampling techniques. The data analysis techniques used are descriptive statistical tests, statistic infrential tests for hypothesis testing using simple regression analyses.